Benigni mioklonus v spanju pri novorojenčkih - Paro Panjan, Darja (Medicinski razgledi, 1999)
Myoclonic jerks may be a benign condilion if occurring in otherwise healthy newborns as they fall asleep. The authors discuss the pathophysiology and clinical picture of myoclonus in newborns and infants. They report on a newbomwith benign nocturnal myoclonus who was subjected to unnecessary diagnostic and therapeutic procedures because of inaccurate specification of myoclonic jerks. The authors stress the need for early recognition of this benign syndrome, which tends to clear spontaneously and has an excellent prognosis.
Keywords: dojenčki; Myoclonus; Sleep; spanje; Prognosis; mioklonus; Infant, newborn; diagnostika